Thermodynamic study on the V(V)-P(V)-H2O system in acidic leaching solution of vanadium-bearing converter slag - Zhang, Weiguang; Zhang, Tingan; Lv, Guozhi; Cao, Xuejiao; Zhu, Hangyu (Separation and purification technology, 2019)
•Thermodynamic analysis on leaching solution of V-bearing converter slag is studied.•Existence form and extraction behavior of V and P in V(V)-P(V)-H2O system is studied.•V-isopolyacid and P-V heteropolyacid ions in V(V)-P(V)-H2O acidic system are studied.•Extraction experiments results are highly consistent with thermodynamic analysis.•A flow sheet was established on the P-V separation and extraction of vanadium. In order to efficiently extract vanadium and remove phosphorus from acidic leaching solutions of vanadium-bearing converter slag, thermodynamic equilibrium diagrams of V-H2O and V-P-H2O systems were analyzed to understand the transformation rules of the single-core ion, isopolyacid ion, and heteropolyacid ion with changing pH values. The results revealed that, vanadium were predominately present as VO2+ as pH ranging from 0 to 0.5 in the V-H2O and V-P-H2O systems. As the solution became more alkaline, VO2+ gradually transformed into isopolyvanadate anions (V10O286−, HV10O285− and H2V10O284−) in the V-H2O solution ([V5+] = 0.1 mol/L), with maximum mole fraction of ΣV10 (sum of isopolyvanadate anions containing 10 vanadium) being nearly 100% when pH = 2–5.5. While in the V-P-H2O solution ([V5+] = 0.1 mol/L, [P5+] = 0.01 mol/L), VO2+ first transformed into P-V heteropolyacid anions (H5PV14O424−, H4PV14O425− and H3PV14O426−) as 1 ≤ pH ≤ 3.5 due to the existence of phosphorus, and the maximum mole fraction of ΣPV14 (sum of P-V heteropolyacid anions) reached 90.35% at pH = 2. The P-V heteropolyacid anions then transformed into isopolyvanadate anions when pH value ranged from 3.5 to 7, and the maximum mole fraction of ΣV10 was 100% at pH = 5. Verification experiments of the solvent extraction on vanadium and phosphorus in the V-H2O ([V5+] = 0.1 mol/L) and V-P-H2O ([V5+] = 0.1 mol/L, [P5+] = 0.01 mol/L) systems were conducted with trialkylamine-N235. Experimental results showed that the extraction rates of ΣV10 + ΣPV14 in the V-P-H2O solution were always higher than those of ΣV10 in the V-H2O solution as 0.5 ≤ pH ≤ 1.5, and a portion of phosphorus element was extracted in the form of H2PO4− + ΣPV14, which was highly consistent with the thermodynamic analyses. Finally, a process flow sheet was established on the P-V separation followed by efficient phosphorus removal and extraction of vanadium.